Development of a predictive scoring system for identifying difficult laparoscopic cholecystectomy cases based on preoperative factors - Chirag Jha, Sarvagya; Ashokbhai Panchal, Hemang (International Surgery Journal, 2025)
Background: Laparoscopic cholecystectomy (LC) is the preferred treatment for gallstone disease. However, difficult cases often require conversion to open surgery and are associated with higher complications. A standardized scoring system can aid in predicting difficult LC cases, enabling better preoperative planning and patient counseling. This study aims to develop and validate a scoring system based on key preoperative factors to predict difficult LC cases. Methods: This prospective study was conducted at a tertiary healthcare center in India, analyzing 80 patients who underwent LC. Based on previously identified risk factors-including patient-related, biochemical, imaging, and intraoperative variables-a scoring system was developed. Each factor was assigned a weighted score based on its impact on surgical difficulty. The scoring model was validated by assessing correlation with surgical outcomes. Results: Patients were stratified into three risk categories: low (<5 points), moderate (5-9 points), and high (≥10 points). Among patients with high scores, 80% required conversion to open surgery, 60% developed postoperative complications, and their hospital stay was significantly prolonged (p<0.05). In contrast, low-score patients had no conversions and minimal complications. The scoring system demonstrated strong predictive capability (AUC=0.87, p<0.001). Conclusions: This predictive scoring system effectively identifies difficult LC cases. Its application can optimize surgical planning, minimize adverse outcomes, and improve patient selection for early open surgery.